2022
DOI: 10.1002/14651858.cd012717.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Splinting for the non-operative management of developmental dysplasia of the hip (DDH) in children under six months of age

Abstract: Splinting for the non-operative management of developmental dysplasia of the hip (DDH) in children under six months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…8 The use of orthoses, such as Pavlik harness, in early infancy for various reasons can potentially impact healthy musculoskeletal development. 6,[9][10][11][12] Our results indicate that non-operative treatment of DDH with the Pavlik harness did not significantly affect the infant's ability to sit unaided or walk independently. Although the Pavlik harness restricts hip adduction and extension, it does not affect lower extremity muscle activities as it allows for active hip movements, as demonstrated by Siddicky et al 10 Zgoda et al 13 evaluated the locomotor development of 100 DDH patients treated with the Koszla abduction brace.…”
Section: Discussionmentioning
confidence: 95%
“…8 The use of orthoses, such as Pavlik harness, in early infancy for various reasons can potentially impact healthy musculoskeletal development. 6,[9][10][11][12] Our results indicate that non-operative treatment of DDH with the Pavlik harness did not significantly affect the infant's ability to sit unaided or walk independently. Although the Pavlik harness restricts hip adduction and extension, it does not affect lower extremity muscle activities as it allows for active hip movements, as demonstrated by Siddicky et al 10 Zgoda et al 13 evaluated the locomotor development of 100 DDH patients treated with the Koszla abduction brace.…”
Section: Discussionmentioning
confidence: 95%
“…50 In fact, the AI is an essential objective measurement to evaluate hip dysplasia, namely in children from 4 months to 8 years old. 51 The optimal duration of PH treatment remains controversial; 47,52 the individualization of the treatment is recommended for each hip without strict time limits. 11 Multiple studies reported the mean duration of PH treatment to be between 8 and 11.7 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing the nonoperative treatment strategy of infant DDH is important to improve outcomes, minimize complications, and reduce the need for surgical intervention. 2…”
Section: Introductionmentioning
confidence: 99%
“…3,4 As a result, published principles of DDH treatment are broadly permissive, which perpetuates wide practice variation and limits the ability to rigorously compare treatments and improve pathways. 2,5-7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation